Knole House
Knole house was built by Thomas Bouchier, Archbishop of Canterbury, for his successors until Archbishop Cranmer gave it over to Henry VIII. Queen Elizabeth subsequently granted it to Thomas Sackville who enlarged it with the addition of this Dutch gable elevation. The house also contains an ornamental stairway which set a new fashion in domestic architecture.